Oral Squamous Cell Carcinoma: A Clinical Case Report - Basanta Kumar Choudhury1 , Saswati Priyadarsini2 , Sandeep Mohanty3 , Shayeri Niyogi4 , Pinali Das5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most common carcinoma affecting the oral mucosa is oral squamous cell carcinoma, with prevalenceseen in the age groups above 50 years in males and with rare occurrence below 30 years. Studies revealapproximately 30-40 % of deaths in oral squamous cell carcinoma occur due to various tissue abuse habits.The present case definesa classic incident of oral squamous cell carcinoma concerning the alveolo-buccalsulcus in a male having 50 years of age.